THE BALANCE OF LEARNING MODEL DEVELOPMENT AT ELEMENTARY SCHOOL AGE - Widiastuti Widiastuti; Tomy Ariyanto (Program Pascasarjana Universitas Negeri Jakarta, 2015)
This research aims to produce a balance learning model for elementary school age. This study used Research & Development (R&D) method. Instrument used in this research is balance a Modified Test of Dynamic Balance applied to collect data in children of elementary school age. Those step are: (1) need analysis, (2) expert justment; (3) limited trial (small group trial); and (4) main trial (field testing). Effectiveness of implementation of balance learning model in children of elementary school age using sample of 70 students by